Emba Ndi Voondre Kyiro Kwori Ro Gboko Amiro Ro Buku Ävuoso’ba Ro (To’dina). Voondre, Losi Oye Lidri Azibe, Tase Ale Be Oyeni Ndi Äduro Losi Se Oyero Aro Te Siro Siro: Buku Giŗingwa 3 Alodi Nätu (3) Ro - Vernooy, Ronnie; Bessette, Guy; Sthapit, Bhuwon; Porcuna Ferrer, Anna (2023)
This handbook in the Moru language of South Sudan is a companion to (https://hdl.handle.net/10568/81286). The three booklets making up this handbook were written and designed for rural producers who are interested in establishing, supporting, and managing a community seed bank. Each booklet focuses on a theme presented by the members of a community seed bank in Africa, Asia, and Latin America.